Modelo de pronóstico de Edas e Iras, hospital I Albrecht Rall-Essalud durante el periodo enero 2011-junio 2017 - Burgos Arteaga, Jenry Euclides (2017)
The present investigation was carried out to determine the prognostic model that best describes the behavior of acute diarrheal diseases (ADDS) and acute respiratory infections (ARIS) in the Hospital I Albrecht RaLL-EsSalud, during the period January 2011 to June 2017, evaluating 78 months. We used the Box Jenkins methodology (Identification, estimation, adequacy test and forecast and validation) and the Eviews 9.0 program for Windows. The forecast period was the last semester of 2017 from July to December 2017. The estimated model for the series of acute diarrheal diseases (ADDS) is an ARIMA(12,1,1) model with an equation:_x000D_ 683693.0-572197.0112^ttttADDSADDSADDS_x000D_ and the model estimated for the series of acute respiratory infections (ARIS) is an ARIMA(1,1,1) model with an equation:_x000D_ ARIS .9077650-3645594.011^ttttARISARIS_x000D_ ,_x000D_ appropriate and with validity of prognosis.